Willy Wonka’s Narcissistic Personality in Roald Dahl’s Charlie and the Chocolate Factory - Pratama, Bovis Narendra; Aji, G. Fajar Sasmita (Journal of Language and Literature, 2017)
Charlie and the Chocolate Factory by Roald Dahl is one of the most popular children’s novels. This novel talks about the adventure of five children who have the opportunity to pay a visit to the most famous chocolate factory in the world, Wonka’s. This study aims to reveal Wonka’s personality disorder as well as the cause of the disorder. The first objective is to identify Willy Wonka’s characteristics. Then, the second objective is to reveal Wonka’s personality disorder and to explain the causes of the disorder.The analysis shows that Willy Wonka is innovative, flamboyant, stubborn, arrogant, and authoritarian. He loves to be the center of attention by putting on outrageous attire. He cannot stand questions and considers them as criticisms or threat. He always brags the products he creates to his guests. Lastly, he always wants to take control of every situation, including taking control of his successor. The last four characteristics mentioned imply that Wonka has narcissistic personality disorder. There are three causes of Willy Wonka’s personality disorder. The first cause is living alone for years without any direct contact with human beings. He exiles himself from the society for years; he only pays attention to himself. The second cause is constantly being media frenzy. People give so much credit to his products and gradually he thinks that he is the best for everything because the society already thinks so. The third cause is the spies who pretend to be his employees and try to steal his recipes. He becomes really devastated because of the tragedy. He fires all of his employees and chooses to never come out of the factory ever again. He has lost his trust on people, and he is too afraid to be betrayed by his workers for the second time. Keywords: narcissistic personality disorder, Freudian psychoanalysis, Roald Dahl